Studies on carbon sequestration potential of trees with epiphytic orchid association - Deepthi, A. S.; Joseph, Nisha; Thomas, Rogimon P.; Karnaver, Preetha; Binu, Maria Susan (Current Botany, 2025)
Epiphytic orchids are a fascinating group of plant species that thrive on the branches and trunks of trees, forming intricate symbiotic relationships with their host. They contribute to the vibrant biodiversity of forest ecosystems and play a crucial role in carbon dynamics and storage. The study aims to estimate carbon sequestrations of phorophytes and associated epiphytic orchids by quantifying the above ground biomass (AGB), total biomass (TB), and amount of carbon stored. It has been found that 97 trees from nine different tree species are associated with epiphytes in the study area. Among the nine species examined, Alstonia scholaris exhibited the highest biomass for above ground, below ground, and total biomass, with values of 24,043.35 kg/tree, 6,251.27 kg/tree, and 30,294.62 kg/tree, respectively. In addition, Cocos nucifera had the lowest values. The highest biomass, carbon storage, and rate of carbon sequestration were recorded for the epiphyte species associated with the phorophyte A. scholaris. When the phorophytes were associated with epiphytic orchids, their carbon sequestration rates rose from 1.94% to 15.07%. This study provides empirical evidence and analytical perspectives to create a model that mitigates the consequences of climate change and global warming while maintaining current land usage.